Knowledge and practices of health care workers at Medunsa Oral Health Centre regarding post exposure prophlaxis for blood-borne viruses - Nkambule, Ntombizodwa R. (University of Limpopo (Medunsa Campus), 2011)
Background: Health care workers (HCWs) are prone to occupational exposures to blood-borne viruses (BBVs), which include hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV). Post exposure prophylaxis (PEP) is available for both HBV and HIV, and if administered correctly can reduce the risk of HBV and HIV transmission by 80%. This study investigated the knowledge and practices of HCWs regarding PEP for BBVs at Medunsa Oral Health Care Centre (MOHC). Methods: This was a cross sectional study conducted among 166 HCWs at the MOHC using a self-administered, anonymous questionnaire on knowledge and practices of HCWs regarding PEP for BBVs. Binary logistic regression method was used to determine factors associated with reporting an occupational exposure and uptake of PEP. Results: The response rate was 67%. The mean age was 27yrs (SO =7.67yrs), and 68.7% of . respondents were female. The overall knowledge regarding PEP among the HCWs was inadequate as 46.9% had poor knowledge. The majority (77.7% [128/166]) of HCWs experienced occupational exposures and amongst them 39.0% (50/128) experienced it twice or more. Almost two-thirds (60.9%) of HCWs experienced an occupational exposure while performing scaling and polishing. Only 28.9% (37/128) of those who were potentially exposed to a BBV reported the incident to the authorities. Out of those who reported, 37% (14/37) took PEP for HIV, and 32.4% (12/37) took PEP for HBV. Among those taking HIV PEP, 21.4% (3/14) indicated that they completed the course. HCWs who haq five or more years of experience j were less likely (OR=0.138, p=0.043) to report compared to those who had less than five years of experience. Conclusion: Overall, participants' knowledge regarding PEP as well as reporting of an exposure was inadequate. The majority of HCWs experienced an occupational exposure while performing scaling and polishing.
Thesis (MPH) -- University of Limpopo, 2011.
Keywords: Prophylaxis; Health care workers